O planejamento estratégico como garantia da atuação administrativa constitucionalmente adequada - Lang, João Marcelo (Universidade do Vale do Rio dos Sinos, 2015)
In the rule of law, even for being fruit of the background models (State of Law and Liberal State Social Law), must not only meet the needs and convenience of the citizens-administered, but above all must act in order to realize the Federal Constitution and to obtain, as a last result, the efficiency / effectiveness of this act. Public policies to be developed in a democratic state, in public administration, are not available to mere administrator will. On the contrary, the Public Administration is increasingly subject to and bound by the legal dictates, not only the legality of idea (formal), but mainly on the grounds of legality (substantial) by which legitimacy, efficiency and effectiveness of the results administrative action are pressing. The Public Administrator is an interpreter of the law and, as such, must act realizing the constitutional principles in order to obtain the optimal result. To act, pending the Administration optimal behavior, acting great, the best solution, the realization of ideal conduct, the setting, the great providence, the embodiment of good administration with the optimum outcome achievement that is the true common good . This "right decision" expected of the administrative act is possible only when the Administrator "take the Constitution seriously," when she realizes that the Public Administration is "constitutionalized" and realize that their function is to achieve the fundamental constitutional rights. To achieve this, the great result, good administration, efficient and effective, it is necessary more than comply with legal formalities involved in the act of editing; it is necessary to perform more serious and wide finalistic control, result. Should plan administrative activities, strategic planning that will serve for a strategic management. This is the "Hercules public administrator", the Administrator who is aware and conscious of all their roles and duties, which plans its administrative operations, standardizing it using the budget laws (multi-annual plan, budget guidelines and the annual budget) and linking himself to them, allowing the citizen to control the administrative act, and especially part of their training. Strategic planning is to select goals, focuses on relevant issues, determine pressing needs, think about what is really important and define the means to achieve them. But do not just plan: you must link to the planning so that, from it, give up strategically. The act of planning allows to develop the sense of direction in the future because it requires of those who plan to secure, from the knowledge of the external environment and internal environment, the vision / mission of the organization, going to the formulation and implementation of actions strategic for at the end of the process, analyze the efficiency and the effectiveness of actions, feeding the system. Along with the strategic plan is the Strategic Management, which consists of a continuous and iterative process of the organization to the environment, allowing constant adaptation of planning to obtain the objectified and advantageous positive results. The "Hercules Public Administrator" is this leading public administrator, monitoring, evaluating, which manages, which defines objectives, which instills values to their subordinates and them and they listen and shares experiences, redirecting them carefully every day, to act in order to meet the aspirations of society for a better and dignified life.
Keywords: Estado democrático de direito; Administração pública; Planejamento estratégico; Administração estratégica; Administrador público Hércules; Rule of law; Public administration; Strategic planning; Strategic management; Hercules public administrator; ACCNPQ::Ciências Sociais Aplicadas::Direito